'Fit to play': Labour market behaviour in a cohort of public-sector antiretroviral treatment patients. Issue 5 (2nd September 2016) - Booysen, Frederik Le Roux; Geldenhuys, Jean-Pierre
ABSTRACT: Given the rapid scale-up of antiretroviral treatment (ART), it is necessary to explore the impact of ART on labour force participation, employment and labour productivity. This article investigates labour market outcomes in a prospective cohort of public-sector ART clients in the Free State province of South Africa. Empirical results suggest that labour force participation increased markedly as the proportion of those too ill to work declined, becoming indistinguishable from participation rates in the general population. Unemployment rates, however, remain above those reported for the general population. ART and its health-related benefits therefore translate into increases in labour force participation, but not employment. Employment status at HIV diagnosis strongly predicts absorption in the labour force. Public-sector ART clients should be referred to vocational rehabilitation and occupational therapy programmes, and to welfare-to-work programmes, and the unskilled to adult education and training and further education and training programmes.